Pengembangan Aplikasi Penerimaan Peserta Didik Baru Berbasis Web Menggunakan Metode Agile - Rahman, Taufik; Ramdani, Muhammad Farhan; Kuswanto, Herman (Jurnal Ilmiah SINUS, 2026)
This study aims to develop a web-based New Student Admissions (PPDB) application that simplifies the registration process, improves administrative efficiency, and ensures the accuracy of prospective student data. The development method used is Agile, which allows for iterative system design with user input at every stage of development. Data was collected through application trials with respondents consisting of school staff and prospective students, and analyzed using quantitative and qualitative approaches to assess ease of use, efficiency, and user satisfaction. The results showed that 90% of respondents considered the application to simplify registration, 85% of staff reported reduced administrative time, and 87% of users were satisfied with the available system. The system successfully collected and verified prospective student data with up to 92% accuracy, and generated registration reports quickly and accurately. These findings confirm that the application of Agile methods in the development of a web-based PPDB application is effective in meeting school administrative needs and improving user experience, while providing a basis for the development of similar systems in other educational institutions.